St. Matthew's Gospel [electronic resource] : translated into the language of the Ojibbeway [sic] Indians in the Diocese of Moosonee - Sanders, J.; Horden, John, 1828-1893. (London : Society for Promoting Christian Knowledge, 1880)
Electronic reproduction. Mode of access: Internet. 44